We'll need the slope formula which is
![m = (y_(2) - y_(1))/(x_(2) - x_(1))\\\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/qmewy2gb06h8udycxh3847pot8qmd2219t.png)
We subtract the y values together, and divide that over the difference in the x values when subtracted in the same order.
Let's find the slope of line DE
![D = (x_1,y_1) = (6,1) \text{ and } E = (x_2,y_2) = (2,3)\\\\m = (y_(2) - y_(1))/(x_(2) - x_(1))\\\\m = (3 - 1)/(2 - 6)\\\\m = (2)/(-4)\\\\m = -(1)/(2)\\\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/yj6if25xp4czrlcarenpq4m2ucpjquhwrk.png)
The slope of line DE is -1/2.
Next, compute the slope of line EF
![E = (x_1,y_1) = (2,3) \text{ and } F = (x_2,y_2) = (-1,-3)\\\\m = (y_(2) - y_(1))/(x_(2) - x_(1))\\\\m = (-3 - 3)/(-1 - 2)\\\\m = (-6)/(-3)\\\\m = 2\\\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/673ouk1ij60dizlgoz2dhtamff894zzknp.png)
The slope of line EF is 2.
Lastly, compute the slope of line FD
![F = (x_1,y_1) = (-1,-3) \text{ and } D = (x_2,y_2) = (6,1)\\\\m = (y_(2) - y_(1))/(x_(2) - x_(1))\\\\m = (1 - (-3))/(6 - (-1))\\\\m = (1 + 3)/(6 + 1)\\\\m = (4)/(7)\\\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/5qr7l4iwi0yj9z9eayh0hzs82g1d8pgmm4.png)
The slope of line FD is 4/7.
--------------------------
To recap everything so far, we found the following:
- slope of DE = -1/2
- slope of EF = 2
- slope of FD = 4/7
The product of the first two slopes gets us (-1/2)*(2) = -1 showing that DE is perpendicular to EF.
Perpendicular slopes multiply to -1 as long as neither line is vertical nor horizontal.
Since DE is perpendicular to EF, this proves we have a 90 degree angle at point E.
Therefore triangle DEF is a right triangle.